Evaluating the impact of seismic surveying on American plaice (Hippoglossoides platessoides) movement using acoustic telemetry in an offshore marine environment - Benjamin G.C. King; Khanh Q. Nguyen; Michael Piersiak; Pablo Borys; Coady Fitzpatrick; Jacqueline M. Hanlon; Dylan O'Neill; Corey J. Morris (Marine Pollution Bulletin, 2026)

Invasive macroalgae exert stronger effects than elevated CO₂ on seagrass (Posidonia oceanica) seedling performance and associated microbiomes - Iris E. Hendriks; Julia Máñez-Crespo; Clea N. van de Ven; R. Sean Fitzpatrick; Alberto V. Borges; Willy Champenois; Tania Aires; Aschwin H. Engelen; Gerard Muyzer; J. Arie Vonk; Fiona Tomas (Marine Pollution Bulletin, 2026)

Associations between metabolic dysfunction–associated steatotic liver disease and physical and mental health–related quality of life in older adults - Marzieh Nasr Azadani; Mojtaba Lotfaliany; Najmeh Davoodian; Michael Berk; Robyn L. Woods; Joanne Ryan; John J. McNeil; Julie A. Pasco; Nigel Stocks; Stuart K. Roberts; William Kemp; Ammar Majeed; et al. (GeroScience, 2026)

Lung cancer risk in relation to indicative radon atlas metrics in Northern Ireland: a population-based case–control study using secondary data - Claire M. Delargy; Helen G. Coleman; Quentin G. Crowley; Damien Bennett; Javier Elio; Deirdre Fitzpatrick; Helen Mitchell; Sara M. Wallace; Rawan A. N. Alhattab; Angela Scott; Bernadette McGuinness; Ruth F. Hunter; et al. (Environmental Geochemistry and Health, 2026)
Radon is an established lung carcinogen, but more research is needed to inform whether area-based measures of radon exposure reflect underlying cancer risk. This study, the first of its kind in the UK, aimed to investigate the association between a nationwide indicative radon atlas and lung cancer risk in Northern Ireland, a region in which lung cancer screening programmes are under design. A population-based case–control study was conducted. Primary lung cancer cases ( n = 1,687) from the Northern Ireland Cancer Registry diagnosed in 2006 and 2014 were compared with 8,094 non-lung cancer controls from a large cohort. Radon exposure data were extracted from the Indicative Atlas of Radon, which categorises 1 km 2 areas by the percentage of households exceeding 200 Bq/m 3 . Exposure data were linked to participants by postcode. Logistic regression models adjusted for age, sex, smoking status, deprivation and PM 2.5 exposure were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for lung cancer. Individuals residing in high radon exposure areas (Atlas Class 6) had a greater than two-fold lung cancer risk (adjusted OR: 2.24, 95% CI: 1.25, 3.92) compared to residents in all other areas. This association was revealed after adjusting for PM 2.5 . This study supports the utility of an indicative radon atlas in reflecting underlying population lung cancer risk associated with radon, while highlighting constraints inherent to atlas-based exposure classification and secondary data.

Breathing lung-on-chip: a versatile tool for assessing respiratory toxicity across multiple therapeutic modalities - Linnea Johansson; Giulia Raggi; James Cartwright; Johnny Lindqvist; Laurène Froment; Patrik Andersson; Catherine Betts; Jorrit J. Hornberg; Nina Hobi; Anna Ollerstam; Paul Fitzpatrick (Archives of Toxicology, 2026)

Release of β-casomorphin-7 in A1/A1 and A2/A2 dairy systems: Insights from simulated semi-dynamic gastrointestinal digestion - Davor Daniloski; Noel A. McCarthy; Todor Vasiljevic; Neha Sharma; Conor J. Fitzpatrick; André Brodkorb; Thao T. Le; Lotte J. Knudsen; Lotte B. Larsen; Nina A. Poulsen (Food Chemistry, 2026)

Assessment of Fellowship Didactic Curricula in Hematology/Oncology: Cross-Sectional Findings From the PODCAST-HOF Trial - Ronak H. Mistry; Karine Tawagi; Daniel J. Hausrath; Samantha A. Armstrong; Inas A. Abuali; Ankoor N. Biswas; Srijan Valasapalli; Pranali S. Pachika; Moriah K. Forster; Ericson Stoen; Yurhee Lee; Giuliana G. Berardi; et al. (Journal of Cancer Education, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

High-altitude Martian plume is likely an ordinary twilight cloud - M.M.J. Crismani; M.S. Chaffin; K. Connour; N.M. Schneider; S. Curry; J. Deighan; R. Fitzpatrick; S. Jain; G. Liuzzi; M. Slipski; G.L. Villanueva (Icarus, 2026)

Long-term air pollution exposure and gait speed decline among older Adults: A longitudinal analysis - Boeun Kim; Anjum Hajat; Amanda J. Gassett; Claire E. Adam; Joel D. Kaufman; Erin O. Semmens; Cindy S. Leary; Annette L. Fitzpatrick (Environmental Research, 2026)

Mapping blue carbon ecosystems from Earth observations at a national scale for Papua New Guinea - Christopher J. Owers; Richard M. Lucas; Carole Planque; Daniel Clewley; Matt Paget; Chloe Fitzpatrick; Annette Burke; Freddie Alei; Mitchell B. Lyons; Andrew D. L. Steven (Frontiers in Marine Science, 2025)
National maps are essential to support the conservation, restoration, and sustainable management of blue carbon ecosystems (BCE). This is particularly important for nations in the Indo-Pacific region, including Papua New Guinea (PNG), that aspire to integrate these ecosystems into their nationally determined contributions (NDCs) for ecosystem accounting. This study focussed on mapping the extent of BCEs in PNG using Earth observation data for the year 2020 and reporting on biomass and carbon storage services. Land cover categories were generated using the Living Earth framework for the 15 coastal provinces of PNG. The total BCE area in PNG (14,353 km²) comprised 30% mangrove, 65% lowland peat swamp forest, 3% saltmarsh, and 2% seagrass. Lowland peat swamp forests contribute the greatest biomass (137.94 ± 67.10 Tg) followed by mangroves (71.79 ± 27.16 Tg), with a total biomass of 212.99 ± 95.89 Tg. Across PNG, a total of 710.46 ± 362.75 Tg C were estimated for belowground carbon of BCEs (reporting to 1 m depth), almost seven times more than that of aboveground carbon (102.14 ± 45.97 Tg C). This study highlights the need for a consistent and standardised framework for mapping BCEs, which can support coordinated management of coastal landscapes across provinces that contribute to national policies and NDC reporting. This case study can be used as a demonstration for other nations where similar opportunities and challenges may exist for mapping BCE using Earth observations, with a framework that can be compared and adapted to user requirements.

Evaluating uncertainties with sample-collection method and source selection in sediment fingerprinting: an example from a Great Lakes tributary - Tanja N. Williamson; James D. Blount; Heidi M. Broerman; Faith A. Fitzpatrick; Isaac J. Mevis; Dayle J. Hoefling; Shannon M. Pace; Matthew J. Komiskey; Rebecca M. Kreiling (Journal of Soils and Sediments, 2025)
Purpose Identifying suspended-sediment (SS) sources, seasonal variability, and phosphorus (P) transported with SS is critical information for basin managers, although there may be concerns about comparability between flow-integrated SS samples used for sediment fingerprinting and discrete samples used for concentrations and loads in basins where SS is mostly silt + clay and(or) one land-use predominates. Objectives were to determine if (1) sample-collection method and (2) source consideration influenced apportionment of the largest SS source. Methods Concurrent-replicate, SS samples were collected during 2022 from the East River, Wisconsin using an automated sampler, commonly used for water-quality sampling, and passive samplers, frequently used for SS fingerprinting. Samples were evaluated for differences in physical and chemical characteristics that may affect source apportionment. Considered sources included three upland land-use (cropland, forest, and roads), two in-channel (streambank and streambed sediment), and one that connects uplands to the stream channel (gullies). Source apportionment used established methods in the SedSAT tool. Source scenarios included land-use + streambank (4src), 4src + gully, 4src + streambed, and 4src + gully + streambed (6src). Results There were no statistically significant differences in median grain size, organic carbon, or sediment-bound P as a function of collection method. In-channel sources were the largest proportional SS source, regardless of season, hydrologic condition, collection method, or source scenario. Source verification highlighted which source fingerprints were most accurately defined and implications for SS target apportionment. Conclusion Varying the source scenarios for sediment fingerprinting indicated that improved management of hydrologic connectivity between upland land use and the stream channel has the potential to mitigate SS loads.

Community engagement in the context of cancer: scoping review of definitions and measures to inform program-level analysis - Heidi J. Keeler; Regina Idoate; Brooke J. Fitzpatrick; Emma Hymel; Josiane Kabayundo; Krishtee Napit; Cynthia M. Schmidt; Shinobu Watanabe-Galloway (Cancer Causes & Control, 2025)

Cannflavin A inhibits TLR4-induced chemokine and cytokine expression in human macrophages - John-Mark K. Fitzpatrick; Diarmuid O’Riordan; Eric J. Downer (Natural Product Research, 2025)

Pyrethroid insecticide pollution of wetlands reduces amphipod density - Breanna R. Keith; Danelle M. Larson; Carl W. Isaacson; Michael J. Anteau; Megan J. Fitzpatrick; Jake D. Carleen (Ecotoxicology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Innovative Systems Engineering Solutions for Power-Positive Operations: Navigating the Multi-Constraint Challenges of the SWARM-EX CubeSat Mission - David J. Fitzpatrick; Scott E. Palo (Advances in Space Research, 2025)

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Density dependence maintains long‐term stability despite increased isolation and inbreeding in the Florida Scrub‐Jay - Jeremy Summers; Elissa J. Cosgrove; Reed Bowman; John W. Fitzpatrick; Nancy Chen (Ecology Letters, 2024)
Isolation caused by anthropogenic habitat fragmentation can destabilize populations. Populations relying on the inflow of immigrants can face reduced fitness due to inbreeding depression as fewer new individuals arrive. Empirical studies of the demographic consequences of isolation are critical to understand how populations persist through changing conditions. We used a 34‐year demographic and environmental dataset from a population of cooperatively breeding Florida Scrub‐Jays ( Aphelocoma coerulescens ) to create mechanistic models linking environmental and demographic factors to population growth rates. We found that the population has not declined despite both declining immigration and increasing inbreeding, owing to a coinciding response in breeder survival. We find evidence of density‐dependent immigration, breeder survival and fecundity, indicating that interactions between vital rates and local density play a role in buffering the population against change. Our study elucidates the impacts of isolation on demography and how long‐term stability is maintained via demographic responses.

Species identification of modern and archaeological shark and ray skeletal tissues using collagen peptide mass fingerprinting - Michael Buckley; Ellie-May Oldfield; Cristina Oliveira; Clara Boulanger; Andrew C. Kitchener; Nicole R. Fuller; Traci Ardren; Victor D. Thompson; Scott M. Fitzpatrick; Michelle J. LeFebvre (Frontiers in Marine Science, 2024)
Introduction Elasmobranchs, such as sharks and rays, are among the world’s most endangered vertebrates, with over 70% loss in abundance over the past 50 years due to human impacts. Zooarchaeological baselines of elasmobranch diversity, distribution, and exploitation hold great promise for contributing essential historical contexts in the assessment of contemporary patterns in their taxonomic diversity and vulnerability to human-caused extinction. Yet, the historical ecology of elasmobranchs receives relatively less archaeological attention compared to that of ray-finned fishes or marine mammals, largely due to issues of taxonomic resolution across zooarchaeological identifications. Methods We explore the use of Zooarchaeology by Mass Spectrometry (ZooMS) for species identification in this unstudied group, using an archaeological case study from the marine environments of the Florida Keys, a marine biodiversity hotspot that is home to an array of elasmobranch species and conservation efforts. By comparison with 39 modern reference species, we could distinguish 12 taxa within the zooarchaeological assemblage from the Clupper archaeological site (Upper Matecumbe Key) that included nine sharks, two rays and a sawfish. Results and discussion The results indicate that, through additional complexity of the collagen peptide mass fingerprint, obtained due to the presence of the cartilaginous type II collagen, ZooMS collagen peptide mass fingerprinting provides exceptionally high taxonomic resolution in this group, yielding species-level identifications in all cases where sufficient reference material was used. This case study also highlights the added value of ZooMS for taxa that are more difficult to distinguish in zooarchaeological analyses, such as vertebrae of the Atlantic sharpnose shark ( Rhizoprionodon terraenovae ) and the hammerhead sharks ( Sphyrna spp.) in the Florida Keys. Therefore, the application of collagen peptide mass fingerprinting to elasmobranchs offers great potential to improve our understanding of their archaeological past and historical ecology.

Cheddar cheese production, structure and in-vitro semi-dynamic gastric digestion: The role of β-casein phenotype - Davor Daniloski; Richard M. Page; Prabin Lamichhane; Conor J. Fitzpatrick; Todor Vasiljevic; André Brodkorb; Mark Timlin; John Paul Murphy; Tom F. O'Callaghan; Noel A. McCarthy (Food Research International, 2024)

P07-09 Spatio-temporal multi-omics analysis of lung tissue and matched biofluids identifies circulatory safety biomarkers for monitoring inhaled drug induced lung injury - M.M. Majumder; E. Williams; M.O. Lindvall; A. Jarnuczak; G. Hamm; C. Di Poto; A.A. Iannetta; J.L. Touza; E.L. Allman; E. Miele; J. Lindgren; E. Sand; et al. (Toxicology Letters, 2024)

A novel in vitro high-content imaging assay for the prediction of drug-induced lung toxicity - Paul A. Fitzpatrick; Julia Johansson; Gareth Maglennon; Ian Wallace; Ramon Hendrickx; Marianna Stamou; Kinga Balogh Sivars; Susann Busch; Linnea Johansson; Natalie Van Zuydam; Kelley Patten; Per M. Åberg; et al. (Archives of Toxicology, 2024)
The development of inhaled drugs for respiratory diseases is frequently impacted by lung pathology in non-clinical safety studies. To enable design of novel candidate drugs with the right safety profile, predictive in vitro lung toxicity assays are required that can be applied during drug discovery for early hazard identification and mitigation. Here, we describe a novel high-content imaging-based screening assay that allows for quantification of the tight junction protein occludin in A549 cells, as a model for lung epithelial barrier integrity. We assessed a set of compounds with a known lung safety profile, defined by clinical safety or non-clinical in vivo toxicology data, and were able to correctly identify 9 of 10 compounds with a respiratory safety risk and 9 of 9 compounds without a respiratory safety risk (90% sensitivity, 100% specificity). The assay was sensitive at relevant compound concentrations to influence medicinal chemistry optimization programs and, with an accessible cell model in a 96-well plate format, short protocol and application of automated imaging analysis algorithms, this assay can be readily integrated in routine discovery safety screening to identify and mitigate respiratory toxicity early during drug discovery. Interestingly, when we applied physiologically-based pharmacokinetic (PBPK) modelling to predict epithelial lining fluid exposures of the respiratory tract after inhalation, we found a robust correlation between in vitro occludin assay data and lung pathology in vivo, suggesting the assay can inform translational risk assessment for inhaled small molecules.

Fish Invasion of Prairie Pothole Wetlands Reduces Amphipod Abundance, A Key Vertebrate Forage - Jake D. Carleen; Danelle M. Larson; Michael J. Anteau; Megan J. Fitzpatrick; Andrew W. Hafs; Carl W. Isaacson; Breanna R. Keith (Wetlands, 2024)

Genetic structure of restored Brook Trout populations in the Southern Appalachian Mountains indicates successful reintroductions - Rebecca J. Smith; David C. Kazyak; Matt A. Kulp; Barbara A. Lubinski; Benjamin M. Fitzpatrick (Conservation Genetics, 2024)

Mechanistic safety assessment via multi-omic characterisation of systemic pathway perturbations following in vivo MAT2A inhibition - Valentina Fogal; Filippos Michopoulos; Andrew F. Jarnuczak; Ghaith M. Hamza; Stephanie Harlfinger; Paul Davey; Heather Hulme; Stephen J. Atkinson; Piotr Gabrowski; Tony Cheung; Michael Grondine; Clare Hoover; et al. (Archives of Toxicology, 2024)
The tumour suppressor p16/CDKN2A and the metabolic gene, methyl-thio-adenosine phosphorylase (MTAP), are frequently co-deleted in some of the most aggressive and currently untreatable cancers. Cells with MTAP deletion are vulnerable to inhibition of the metabolic enzyme, methionine-adenosyl transferase 2A (MAT2A), and the protein arginine methyl transferase (PRMT5). This synthetic lethality has paved the way for the rapid development of drugs targeting the MAT2A/PRMT5 axis. MAT2A and its liver- and pancreas-specific isoform, MAT1A, generate the universal methyl donor S-adenosylmethionine (SAM) from ATP and methionine. Given the pleiotropic role SAM plays in methylation of diverse substrates, characterising the extent of SAM depletion and downstream perturbations following MAT2A/MAT1A inhibition (MATi) is critical for safety assessment. We have assessed in vivo target engagement and the resultant systemic phenotype using multi-omic tools to characterise response to a MAT2A inhibitor (AZ’9567). We observed significant SAM depletion and extensive methionine accumulation in the plasma, liver, brain and heart of treated rats, providing the first assessment of both global SAM depletion and evidence of hepatic MAT1A target engagement. An integrative analysis of multi-omic data from liver tissue identified broad perturbations in pathways covering one-carbon metabolism, trans-sulfuration and lipid metabolism. We infer that these pathway-wide perturbations represent adaptive responses to SAM depletion and confer a risk of oxidative stress, hepatic steatosis and an associated disturbance in plasma and cellular lipid homeostasis. The alterations also explain the dramatic increase in plasma and tissue methionine, which could be used as a safety and PD biomarker going forward to the clinic.

Monitoring the effect of consumption temperature of full-fat milk on in vitro gastric digestion using Magnetic Resonance Imaging - Conor J. Fitzpatrick; Maja Musse; Jiajun Feng; Guylaine Collewet; Tiphaine Lucas; Mark Timlin; Sylvain Challois; Stephane Quellec; Didier Dupont; André Brodkorb; Daniela Freitas; Steven Le Feunteun (Food Hydrocolloids, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Impact of feeding regimes and lactation stage on sensory attributes of Cheddar cheese - Lauren McGuinness; Mark Timlin; John P. Murphy; Deirdre Hennessy; Ellen Fitzpatrick; Kieran McCarthy; Michael O'Donovan; Tom F. O'Callaghan; Kieran N. Kilcawley; E. Dolores O'Riordan; Andre Brodkorb; Jeremiah J. Sheehan; et al. (Food Research International, 2024)

Equivalent roles of marine subsidies and island characteristics in shaping island bird communities - Debora S. Obrist; Patrick J. Hanly; Jeremiah C. Kennedy; Owen T. Fitzpatrick; Sara B. Wickham; Wiebe Nijland; Luba Y. Reshitnyk; Chris T. Darimont; Brian M. Starzomski; John D. Reynolds (Journal of Biogeography, 2024)
Aim Species distributions across islands are shaped by dispersal limitations, environmental filters and biotic interactions but the relative influence of each of these processes has rarely been assessed. Here, we examine the relative contributions of island characteristics, marine subsidies, species traits, and species interactions on avian community composition. Location Central Coast region of British Columbia, Canada. Taxon Terrestrial breeding birds. Methods We observed 3610 individuals of 32 bird species on 89 islands that spanned multiple orders of magnitude in area (0.0002–3 km 2 ). We fit a spatially explicit joint species distribution model to estimate the relative contributions of island physical characteristics, island‐specific inputs of marine subsidies, species' traits, and biotic interactions on species distributions. Biogeographic characteristics included island area, isolation, and habitat heterogeneity, while marine influence was represented by forest‐edge soil δ 15 N, wrack biomass, shoreline substrate, and distance to shore. This approach also allowed us to estimate how much variation in distributions resulted from species' biological traits (i.e. body mass, feeding guild, feeding height, and nesting height). Results Bird species distributions were determined almost equivalently by island biogeographic characteristics (23.5% of variation explained) and marine influence (24.8%). We detected variation in species‐specific responses to both island biogeographic characteristics and marine influence, but no significant effect of any biological trait examined. Additionally, we found evidence that habitat preferences were a more important driver than competitive interactions. Main Conclusions Although most island biogeographic studies focus only on islands' physical characteristics, we found evidence for an equivalent role of marine subsidy in structuring island bird communities. Our study suggests that for small islands, disentangling the effects of island biogeographic characteristics, marine inputs, and biotic interactions is a useful next step in understanding species distributions.

Differential gene expression profiling implicates altered network development in rat postnatal day 4 cortex following 4-Methylimidazole (4-MeI) induced maternal seizures - Abdull J. Massri; Mackenzie Fitzpatrick; Helen Cunny; Jian-Liang Li; G. Jean Harry (Neurotoxicology and Teratology, 2023)

Terrestrial carbon isotope stratigraphy of the Eocene–Oligocene transition, Petrockstowe and Bovey basins, Devon, UK - Mohammed S. Chaanda; Stephen T. Grimes; Rhodri M. Jerrett; Mark Anderson; Melanie J. Leng; Meriel E. Fitzpatrick; Gregory D. Price (Proceedings of the Geologists' Association, 2023)

Parallel evaluation of alternative skin barrier models and excised human skin for dermal absorption studies in vitro - Alec T. Salminen; Kelly J. Davis; Robert P. Felton; Nathania Nischal; Linda S. VonTungeln; Frederick A. Beland; Kristy Derr; Paul C. Brown; Marc Ferrer; Linda M. Katz; Nicole C. Kleinstreuer; Jonathan Leshin; et al. (Toxicology in Vitro, 2023)

Mapping soil corrosivity in an Australian arid environment and comparing corrosion rates of exclusion fence netting with different zinc coatings - Andrea D. Stiglingh; Luke M. Mosley; Ronald J. Smernik; Robert W. Fitzpatrick (Geoderma Regional, 2023)

Evaluation of a Prefabricated Fish Passage Design for Great Plains Fishes - Ryan M. Fitzpatrick; David W. Longrie; Ryan J. Friebertshauser; H. Paul Foutz (Fishes, 2023)
Connectivity is critical for stream fish persistence, and fish passage structures are a useful conservation tool to reconnect fragmented systems. The design of fish passage structures is a tradeoff between the area available for construction, slope, and costs associated with the structure. The Longrie–Fecteau fish passage structure was designed to be modular, adjustable to barrier-specific needs, and to have a low slope (2%) to pass small-bodied fishes. We evaluated fish passage through this structure in Fountain Creek, Colorado, USA, via a PIT tag mark–recapture study. We documented four native Great Plains fish species successfully ascending the passage structure, with most passage occurring at night. We estimated a 3% probability of a released fish entering the structure, then 89% and 99% passage to the midpoint and exit of the 123 m structure, respectively. Low entrance efficiency was due to low recapture probability of small-bodied study organisms in a relatively large system, and the low percentage of space of the entryway on this barrier (

Using aerial LiDAR to assess regional availability of potential habitat for a conservation dependent forest bird - Darin J. McNeil; G. Fisher; Cameron J. Fiss; Andrew J. Elmore; Matthew C. Fitzpatrick; Jeff W. Atkins; Jonathan Cohen; Jeffery L. Larkin (Forest Ecology and Management, 2023)

Simulating flood events at the Twin Ports of Duluth-Superior using a linked hydrologic-hydrodynamic framework - Lindsay Fitzpatrick; Daniel Titze; Eric J. Anderson; Dmitry Beletsky; John G. W. Kelley (Ocean Dynamics, 2023)
Generally, ports in the North American Great Lakes are not supported with navigational guidance (water level, water temperature, currents, ice) by NOAA’s Great Lakes Operational Forecast System (GLOFS). To examine the benefit of extending model coverage to this critical infrastructure, a linked hydrologic-hydrodynamic framework was developed for the Twin Ports of Duluth-Superior in western Lake Superior, and tested over three case studies of flooding due to storm surge and/or river flooding. Streamflow from 22 National Water Model (NWM) simulated and 3 gauged inflows within the domain was injected into a hydrodynamic model built on the Finite Volume Community Ocean Model (FVCOM), with a wet-dry grid that covered the harbor and surrounding floodplain. Model results from flood simulations compared well against time-series of water level and streamflow at gauges within the harbor, with root mean square error (RMSE) and bias values small relative to the typical fluctuations. Inclusion of NWM-simulated tributaries improved the accuracy of modeled water levels in the harbor, and increased simulated current speeds in navigational channels by up to 0.5 ms −1 . Modeled inundation extent in the floodplain closely matched flood extent surveys conducted in response to a record flood event in 2012, demonstrating the capability of the modeling framework to provide flood guidance in the complex coastal setting.

Nicotinic and muscarinic acetylcholine receptor antagonism dose-dependently decreases sign- but not goal-tracking behavior in male rats - Ali Gheidi; Christopher J. Fitzpatrick; Jordan D. Gregory; Jonathan D. Morrow (Psychopharmacology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Size-Dependent Effective Diffusivity in Healthy Human and Porcine Joint Synovium - Young Guang; Alexandra L. Davis; Thomas M. McGrath; Christine T. N. Pham; James A. J. Fitzpatrick; Lori A. Setton (Annals of Biomedical Engineering, 2022)

High abundance of a single taxon (amphipods) predicts aquatic macrophyte biodiversity in prairie wetlands - Danelle M. Larson; Demey DeJong; Michael J. Anteau; Megan J. Fitzpatrick; Breanna Keith; Emily G. Schilling; Barry Thoele (Biodiversity and Conservation, 2022)
Conservation programs often aim to protect the abundance of individual species and biodiversity simultaneously. We quantified relations between amphipod densities and aquatic macrophyte (large plants and algae) diversity to test a hypothesis that biodiversity can support high abundance of a single taxonomic group. Amphipods ( Gammarus lacustris and Hyalella azteca ) are key forage for waterfowl and are declining in the Prairie Pothole Region of North America. We sampled a large gradient of amphipod densities (0–7050 amphipods/m 3 ) in 49 semi-permanent wetlands, and 50% of the study wetlands had high amphipod densities (> 500 amphipods/m 3 ). Generalized linear models revealed G. lacustris and H. azteca densities increased exponentially with macrophyte diversity indices. Further, H. azteca densities were greatest at moderate levels of submersed vegetation biomass. Community analyses showed both amphipod species were positively associated with diverse macrophyte assemblages and negatively associated with high coverage of cattails ( Typha spp.), a taxon that creates monotypic stands, as well as bladderwort ( Utricularia spp.), a carnivorous plant. Our results indicate that amphipods could be used as an umbrella species for protecting diverse macrophyte communities in semi-permanent and permanent wetlands of North America’s Prairie Pothole Region.

Advancing Social Equity in and Through Marine Conservation - Nathan J. Bennett; Laure Katz; Whitney Yadao-Evans; Gabby N. Ahmadia; Scott Atkinson; Natalie C. Ban; Neil M. Dawson; Asha de Vos; Juno Fitzpatrick; David Gill; Mael Imirizaldu; Naia Lewis; et al. (Frontiers in Marine Science, 2021)
Substantial efforts and investments are being made to increase the scale and improve the effectiveness of marine conservation globally. Though it is mandated by international law and central to conservation policy, less attention has been given to how to operationalize social equity in and through the pursuit of marine conservation. In this article, we aim to bring greater attention to this topic through reviewing how social equity can be better integrated in marine conservation policy and practice. Advancing social equity in marine conservation requires directing attention to: recognition through acknowledgment and respect for diverse peoples and perspectives; fair distribution of impacts through maximizing benefits and minimizing burdens; procedures through fostering participation in decision-making and good governance; management through championing and supporting local involvement and leadership; the environment through ensuring the efficacy of conservation actions and adequacy of management to ensure benefits to nature and people; and the structural barriers to and institutional roots of inequity in conservation. We then discuss the role of various conservation organizations in advancing social equity in marine conservation and identify the capacities these organizations need to build. We urge the marine conservation community, including governments, non-governmental organizations and donors, to commit to the pursuit of socially equitable conservation.

Do skeletal muscle motor units and microvascular units align to help match blood flow to metabolic demand? - Coral L. Murrant; Nicole M. Fletcher; Eamon J. H. Fitzpatrick; Kinley S. Gee (European Journal of Applied Physiology, 2021)

Size-Dependent Effective Diffusivity in Healthy Human and Porcine Joint Synovium - Young Guang; Alexandra L. Davis; Thomas M. McGrath; Christine T. N. Pham; James A. J. Fitzpatrick; Lori A. Setton (Annals of Biomedical Engineering, 2021)

Can indicator species guide conservation investments to restore connectivity in Great Lakes tributaries? - Kimberly B. Fitzpatrick; Allison T. Moody; Austin Milt; Matthew E. Herbert; Mary Khoury; Eugene Yacobson; Jared A. Ross; Patrick J. Doran; Michael C. Ferris; Peter B. McIntyre; Thomas M. Neeson (Biodiversity and Conservation, 2021)

Snowpack, Tree Size, and Ecological Legacies Promote Seedling Establishment in Tree Islands at the Treeline - O. T. Fitzpatrick; M. Blade; L. A. Fishback; G. P. Kershaw; J. Muffly; S. D. Mamet (Ecosystems, 2020)

How a typical West African day in the future-climate compares with current-climate conditions in a convection-permitting and parameterised convection climate model - Rory G. J. Fitzpatrick; Douglas J. Parker; John H. Marsham; David P. Rowell; Lawrence S. Jackson; Declan Finney; Chetan Deva; Simon Tucker; Rachael Stratton (Climatic Change, 2020)
Current-climate precipitation and temperature extremes have been identified by decision makers in West Africa as among the more impactful weather events causing lasting socioeconomic damage. In this article, we use a plausible future-climate scenario (RCP8.5) for the end of the twenty-first century to explore the relative commonness of such extremes under global warming. The analysis presented considers what a typical day in the future climate will feel like relative to current extrema. Across much of West Africa, we see that the typical future-climate day has maximum and minimum temperatures greater than 99.5% of currently experienced values. This finding exists for most months but is particularly pronounced during the Boreal spring and summer. The typical future precipitation event has a daily rainfall rate greater than 95% of current storms. These findings exist in both a future scenario model run with and without parameterised convection, and for many of the Coupled Model Inter-comparison Project version 5 ensemble members. Additionally, agronomic monsoon onset is projected to occur later and have greater inter-annual variability in the future. Our findings suggest far more extreme conditions in future climate over West Africa. The projected changes in temperature and precipitation could have serious socioeconomic implications, stressing the need for effective mitigation given the potential lack of adaptation pathways available to decision makers.

Future winters present a complex energetic landscape of decreased costs and reduced risk for a freeze‐tolerant amphibian, the Wood Frog ( Lithobates sylvaticus ) - Megan J. Fitzpatrick; Warren P. Porter; Jonathan N. Pauli; Michael R. Kearney; Michael Notaro; Benjamin Zuckerberg (Global Change Biology, 2020)
Winter climate warming is rapidly leading to changes in snow depth and soil temperatures across mid‐ and high‐latitude ecosystems, with important implications for survival and distribution of species that overwinter beneath the snow. Amphibians are a particularly vulnerable group to winter climate change because of the tight coupling between their body temperature and metabolic rate. Here, we used a mechanistic microclimate model coupled to an animal biophysics model to predict the spatially explicit effects of future climate change on the wintering energetics of a freeze‐tolerant amphibian, the Wood Frog ( Lithobates sylvaticus ), across its distributional range in the eastern United States. Our below‐the‐snow microclimate simulations were driven by dynamically downscaled climate projections from a regional climate model coupled to a one‐dimensional model of the Laurentian Great Lakes. We found that warming soil temperatures and decreasing winter length have opposing effects on Wood Frog winter energy requirements, leading to geographically heterogeneous implications for Wood Frogs. While energy expenditures and peak body ice content were predicted to decline in Wood Frogs across most of our study region, we identified an area of heightened energetic risk in the northwestern part of the Great Lakes region where energy requirements were predicted to increase. Because Wood Frogs rely on body stores acquired in fall to fuel winter survival and spring breeding, increased winter energy requirements have the potential to impact local survival and reproduction. Given the geographically variable and intertwined drivers of future under‐snow conditions (e.g., declining snow depths, rising air temperatures, shortening winters), spatially explicit assessments of species energetics and risk will be important to understanding the vulnerability of subnivium‐adapted species.

Seasonal asymmetry of equatorial East African rainfall projections: understanding differences between the response of the long rains and the short rains to increased greenhouse gases - Kerry H. Cook; Rory G. J. Fitzpatrick; Weiran Liu; Edward K. Vizy (Climate Dynamics, 2020)

Effects of the cannabinoid receptor agonist CP-55,940 on incentive salience attribution - Ali Gheidi; Lora M. Cope; Christopher J. Fitzpatrick; Benjamin N. Froehlich; Rachel Atkinson; Coltrane K. Groves; Clair N. Barcelo; Jonathan D. Morrow (Psychopharmacology, 2020)

Delineation of phenotypes and genotypes related to cohesin structural protein RAD21 - Lianne C. Krab; Iñigo Marcos-Alcalde; Melissa Assaf; Meena Balasubramanian; Janne Bayer Andersen; Anne-Marie Bisgaard; David R. Fitzpatrick; Sanna Gudmundsson; Sylvia A. Huisman; Tugba Kalayci; Saskia M. Maas; Francisco Martinez; et al. (Human Genetics, 2020)
RAD21 encodes a key component of the cohesin complex, and variants in RAD21 have been associated with Cornelia de Lange Syndrome (CdLS). Limited information on phenotypes attributable to RAD21 variants and genotype–phenotype relationships is currently published. We gathered a series of 49 individuals from 33 families with RAD21 alterations [24 different intragenic sequence variants (2 recurrent), 7 unique microdeletions], including 24 hitherto unpublished cases. We evaluated consequences of 12 intragenic variants by protein modelling and molecular dynamic studies. Full clinical information was available for 29 individuals. Their phenotype is an attenuated CdLS phenotype compared to that caused by variants in NIPBL or SMC1A for facial morphology, limb anomalies, and especially for cognition and behavior. In the 20 individuals with limited clinical information, additional phenotypes include Mungan syndrome (in patients with biallelic variants) and holoprosencephaly, with or without CdLS characteristics. We describe several additional cases with phenotypes including sclerocornea, in which involvement of the RAD21 variant is uncertain. Variants were frequently familial, and genotype–phenotype analyses demonstrated striking interfamilial and intrafamilial variability. Careful phenotyping is essential in interpreting consequences of RAD21 variants, and protein modeling and dynamics can be helpful in determining pathogenicity. The current study should be helpful when counseling families with a RAD21 variation.

Translational studies of intravenous and intracerebroventricular routes of administration for CNS cellular biodistribution for BMN 250, an enzyme replacement therapy for the treatment of Sanfilippo type B - Anita Grover; Danielle Crippen-Harmon; Lacey Nave; Jon Vincelette; Jill C. M. Wait; Andrew C. Melton; Roger Lawrence; Jillian R. Brown; Katherine A. Webster; Bryan K. Yip; Brian Baridon; Catherine Vitelli; et al. (Drug Delivery and Translational Research, 2020)
BMN 250 is being developed as enzyme replacement therapy for Sanfilippo type B, a primarily neurological rare disease, in which patients have deficient lysosomal alpha- N -acetylglucosaminidase (NAGLU) enzyme activity. BMN 250 is taken up in target cells by the cation-independent mannose 6-phosphate receptor (CI-MPR, insulin-like growth factor 2 receptor), which then facilitates transit to the lysosome. BMN 250 is dosed directly into the central nervous system via the intracerebroventricular (ICV) route, and the objective of this work was to compare systemic intravenous (IV) and ICV delivery of BMN 250 to confirm the value of ICV dosing. We first assess the ability of enzyme to cross a potentially compromised blood–brain barrier in the Naglu −/− mouse model and then assess the potential for CI-MPR to be employed for receptor-mediated transport across the blood–brain barrier. In wild-type and Naglu −/− mice, CI-MPR expression in brain vasculature is high during the neonatal period but virtually absent by adolescence. In contrast, CI-MPR remains expressed through adolescence in non-affected non-human primate and human brain vasculature. Combined results from IV administration of BMN 250 in Naglu −/− mice and IV and ICV administration in healthy juvenile non-human primates suggest a limitation to therapeutic benefit from IV administration because enzyme distribution is restricted to brain vascular endothelial cells: enzyme does not reach target neuronal cells following IV administration, and pharmacological response following IV administration is likely restricted to clearance of substrate in endothelial cells. In contrast, ICV administration enables central nervous system enzyme replacement with biodistribution to target cells.

Temperature and telomeres: thermal treatment influences telomere dynamics through a complex interplay of cellular processes in a cold-climate skink - L. J. Fitzpatrick; M. Olsson; L. M. Parsley; A. Pauliny; T. L. Pinfold; T. Pirtle; G. M. While; E. Wapstra (Oecologia, 2019)

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

How will climate novelty influence ecological forecasts? Using the Quaternary to assess future reliability - Matthew C. Fitzpatrick; Jessica L. Blois; John W. Williams; Diego Nieto‐Lugilde; Kaitlin C. Maguire; David J. Lorenz (Global Change Biology, 2018)
Future climates are projected to be highly novel relative to recent climates. Climate novelty challenges models that correlate ecological patterns to climate variables and then use these relationships to forecast ecological responses to future climate change. Here, we quantify the magnitude and ecological significance of future climate novelty by comparing it to novel climates over the past 21,000 years in North America. We then use relationships between model performance and climate novelty derived from the fossil pollen record from eastern North America to estimate the expected decrease in predictive skill of ecological forecasting models as future climate novelty increases. We show that, in the high emissions scenario (RCP 8.5) and by late 21st century, future climate novelty is similar to or higher than peak levels of climate novelty over the last 21,000 years. The accuracy of ecological forecasting models is projected to decline steadily over the coming decades in response to increasing climate novelty, although models that incorporate co‐occurrences among species may retain somewhat higher predictive skill. In addition to quantifying future climate novelty in the context of late Quaternary climate change, this work underscores the challenges of making reliable forecasts to an increasingly novel future, while highlighting the need to assess potential avenues for improvement, such as increased reliance on geological analogs for future novel climates and improving existing models by pooling data through time and incorporating assemblage‐level information.

Conserving rare species can have high opportunity costs for common species - Thomas M. Neeson; Patrick J. Doran; Michael C. Ferris; Kimberly B. Fitzpatrick; Matthew Herbert; Mary Khoury; Allison T. Moody; Jared Ross; Eugene Yacobson; Peter B. McIntyre (Global Change Biology, 2018)
Conservation practitioners face difficult choices in apportioning limited resources between rare species (to ensure their existence) and common species (to ensure their abundance and ecosystem contributions). We quantified the opportunity costs of conserving rare species of migratory fishes in the context of removing dams and retrofitting road culverts across 1,883 tributaries of the North American Great Lakes. Our optimization models show that maximizing total habitat gains across species can be very efficient in terms of benefits achieved per dollar spent, but disproportionately benefits common species. Conservation approaches that target rare species, or that ensure some benefits for every species (i.e., complementarity) enable strategic allocation of resources among species but reduce aggregate habitat gains. Thus, small habitat gains for the rarest species necessarily come at the expense of more than 20 times as much habitat for common ones. These opportunity costs are likely to occur in many ecosystems because range limits and conservation costs often vary widely among species. Given that common species worldwide are declining more rapidly than rare ones within major taxa, our findings provide incentive for triage among multiple worthy conservation targets.

The interplay of climate and land use change affects the distribution of EU bumblebees - Leon Marshall; Jacobus C. Biesmeijer; Pierre Rasmont; Nicolas J. Vereecken; Libor Dvorak; Una Fitzpatrick; Frédéric Francis; Johann Neumayer; Frode Ødegaard; Juho P. T. Paukkunen; Tadeusz Pawlikowski; Menno Reemer; et al. (Global Change Biology, 2018)
Bumblebees in Europe have been in steady decline since the 1900s. This decline is expected to continue with climate change as the main driver. However, at the local scale, land use and land cover ( LULC ) change strongly affects the occurrence of bumblebees. At present, LULC change is rarely included in models of future distributions of species. This study's objective is to compare the roles of dynamic LULC change and climate change on the projected distribution patterns of 48 European bumblebee species for three change scenarios until 2100 at the scales of Europe, and Belgium, Netherlands and Luxembourg ( BENELUX ). We compared three types of models: (1) only climate covariates, (2) climate and static LULC covariates and (3) climate and dynamic LULC covariates. The climate and LULC change scenarios used in the models include, extreme growth applied strategy ( GRAS ), business as might be usual and sustainable European development goals. We analysed model performance, range gain/loss and the shift in range limits for all bumblebees. Overall, model performance improved with the introduction of LULC covariates. Dynamic models projected less range loss and gain than climate‐only projections, and greater range loss and gain than static models. Overall, there is considerable variation in species responses and effects were most pronounced at the BENELUX scale. The majority of species were predicted to lose considerable range, particularly under the extreme growth scenario ( GRAS ; overall mean: 64% ± 34). Model simulations project a number of local extinctions and considerable range loss at the BENELUX scale (overall mean: 56% ± 39). Therefore, we recommend species‐specific modelling to understand how LULC and climate interact in future modelling. The efficacy of dynamic LULC change should improve with higher thematic and spatial resolution. Nevertheless, current broad scale representations of change in major land use classes impact modelled future distribution patterns.

Microsatellite analysis supports the existence of three cryptic species within the bumble bee Bombus lucorum sensu lato - Lorraine McKendrick; Jim Provan; Úna Fitzpatrick; Mark J. F. Brown; Tómas E. Murray; Eckart Stolle; Robert J. Paxton (Conservation Genetics, 2017)

Golden Eagle fatalities and the continental‐scale consequences of local wind‐energy generation - Todd E. Katzner; David M. Nelson; Melissa A. Braham; Jacqueline M. Doyle; Nadia B. Fernandez; Adam E. Duerr; Peter H. Bloom; Matthew C. Fitzpatrick; Tricia A. Miller; Renee C. E. Culver; Loan Braswell; J. Andrew DeWoody (Conservation Biology, 2017)
Renewable energy production is expanding rapidly despite mostly unknown environmental effects on wildlife and habitats. We used genetic and stable isotope data collected from Golden Eagles (Aquila chrysaetos) killed at the Altamont Pass Wind Resource Area (APWRA) in California in demographic models to test hypotheses about the geographic extent and demographic consequences of fatalities caused by renewable energy facilities. Geospatial analyses of δ 2 H values obtained from feathers showed that ≥25% of these APWRA‐killed eagles were recent immigrants to the population, most from long distances away (>100 km). Data from nuclear genes indicated this subset of immigrant eagles was genetically similar to birds identified as locals from the δ 2 H data. Demographic models implied that in the face of this mortality, the apparent stability of the local Golden Eagle population was maintained by continental‐scale immigration. These analyses demonstrate that ecosystem management decisions concerning the effects of local‐scale renewable energy can have continental‐scale consequences.

Theory of Visual Attention (TVA) applied to mice in the 5-choice serial reaction time task - C. M. Fitzpatrick; M. Caballero-Puntiverio; U. Gether; T. Habekost; C. Bundesen; S. Vangkilde; D. P. D. Woldbye; J. T. Andreasen; A. Petersen (Psychopharmacology, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

An experimental test of relatedness-based mate discrimination in a social lizard - Genevieve Bordogna; George Cunningham; Luisa J. Fitzpatrick; Ben Halliwell; Hannah E. A. MacGregor; Kirke L. Munch; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2016)

Behavioral evidence suggests facultative scavenging by a marine apex predator during a food pulse - Neil Hammerschlag; Ian Bell; Richard Fitzpatrick; Austin J. Gallagher; Lucy A. Hawkes; Mark G. Meekan; John D. Stevens; Michele Thums; Matthew J. Witt; Adam Barnett (Behavioral Ecology and Sociobiology, 2016)

A comparative review of fisheries management experiences in the E uropean U nion and in other countries worldwide: I celand, A ustralia, and N ew Z ealand - Paul Marchal; Jesper Levring Andersen; Martin Aranda; Mike Fitzpatrick; Leyre Goti; Olivier Guyader; Gunnar Haraldsson; Aaron Hatcher; Troels Jacob Hegland; Pascal Le Floc'h; Claire Macher; Loretta Malvarosa; et al. (Fish and Fisheries, 2016)
This study compares the details and performance of fisheries management between the EU and a selection of other countries worldwide: Iceland, New Zealand, and Australia, which are considered in many respects to be among the most advanced in the world in fisheries management. Fisheries management in the EU , Iceland, Australia, and New Zealand has developed following different paths, despite being based on similar instruments and principles. Iceland, Australia, and New Zealand have been at the forefront of developing management practices such as stakeholder involvement, legally binding management targets (Australia, New Zealand), individual transferable quotas, and discard bans (Iceland, New Zealand). The EU has since the beginning of the 21st century taken significant steps to better involve stakeholders and establish quantitative targets through management plans, and a landing obligation is gradually being implemented from 2015 onward. The management of domestic fisheries resources in Australia, New Zealand, and Iceland has, overall, performed better than in the EU , in terms of conservation and economic efficiency. It should, however, be stressed that, compared to Australia, New Zealand, and Iceland, (i) initial over‐capacity was more of an issue in the EU when management measures became legally binding and also that (ii) EU has been progressive in developing common enforcement standards, on stocks shared by sovereign nations. The situation of EU fisheries has substantially improved over the period 2004–2013 in the northeast Atlantic, with fishery status getting close to that in the other jurisdictions, but the lack of recovery for Mediterranean fish stocks remains a concern.

Exercise training comprising of single 20-s cycle sprints does not provide a sufficient stimulus for improving maximal aerobic capacity in sedentary individuals - P. Songsorn; A. Lambeth-Mansell; J. L. Mair; M. Haggett; B. L. Fitzpatrick; J. Ruffino; A. Holliday; R. S. Metcalfe; N. B. J. Vollaard (European Journal of Applied Physiology, 2016)

Adaptive divergence despite strong genetic drift: genomic analysis of the evolutionary mechanisms causing genetic differentiation in the island fox ( Urocyon littoralis ) - W. Chris Funk; Robert E. Lovich; Paul A. Hohenlohe; Courtney A. Hofman; Scott A. Morrison; T. Scott Sillett; Cameron K. Ghalambor; Jesus E. Maldonado; Torben C. Rick; Mitch D. Day; Nicholas R. Polato; Sarah W. Fitzpatrick; et al. (Molecular Ecology, 2016)
The evolutionary mechanisms generating the tremendous biodiversity of islands have long fascinated evolutionary biologists. Genetic drift and divergent selection are predicted to be strong on islands and both could drive population divergence and speciation. Alternatively, strong genetic drift may preclude adaptation. We conducted a genomic analysis to test the roles of genetic drift and divergent selection in causing genetic differentiation among populations of the island fox ( Urocyon littoralis ). This species consists of six subspecies, each of which occupies a different California Channel Island. Analysis of 5293 SNP loci generated using Restriction‐site Associated DNA ( RAD ) sequencing found support for genetic drift as the dominant evolutionary mechanism driving population divergence among island fox populations. In particular, populations had exceptionally low genetic variation, small N e (range = 2.1–89.7; median = 19.4), and significant genetic signatures of bottlenecks. Moreover, islands with the lowest genetic variation (and, by inference, the strongest historical genetic drift) were most genetically differentiated from mainland grey foxes, and vice versa, indicating genetic drift drives genome‐wide divergence. Nonetheless, outlier tests identified 3.6–6.6% of loci as high F ST outliers, suggesting that despite strong genetic drift, divergent selection contributes to population divergence. Patterns of similarity among populations based on high F ST outliers mirrored patterns based on morphology, providing additional evidence that outliers reflect adaptive divergence. Extremely low genetic variation and small N e in some island fox populations, particularly on San Nicolas Island, suggest that they may be vulnerable to fixation of deleterious alleles, decreased fitness and reduced adaptive potential.

Higher Abundance of Marine Predators and Changes in Fishers' Behavior Following Spatial Protection within the World's Biggest Shark Fishery - Vanessa F. Jaiteh; Steve J. Lindfield; Sangeeta Mangubhai; Carol Warren; Ben Fitzpatrick; Neil R. Loneragan (Frontiers in Marine Science, 2016)

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

Fifty years of co‐evolution and beyond: integrating co‐evolution from molecules to species - Diego Carmona; Connor R. Fitzpatrick; Marc T. J. Johnson (Molecular Ecology, 2015)
Fifty years after Ehrlich and Raven's seminal paper, the idea of co‐evolution continues to grow as a key concept in our understanding of organic evolution. This concept has not only provided a compelling synthesis between evolutionary biology and community ecology, but has also inspired research that extends beyond its original scope. In this article, we identify unresolved questions about the co‐evolutionary process and advocate for the integration of co‐evolutionary research from molecular to interspecific interactions. We address two basic questions: (i) What is co‐evolution and how common is it? (ii) What is the unit of co‐evolution? Both questions aim to explore the heart of the co‐evolutionary process. Despite the claim that co‐evolution is ubiquitous, we argue that there is in fact little evidence to support the view that reciprocal natural selection and coadaptation are common in nature. We also challenge the traditional view that co‐evolution only occurs between traits of interacting species. Co‐evolution has the potential to explain evolutionary processes and patterns that result from intra‐ and intermolecular biochemical interactions within cells, intergenomic interactions (e.g. nuclear‐cytoplasmic) within species, as well as intergenomic interactions mediated by phenotypic traits between species. Research that bridges across these levels of organization will help to advance our understanding of the importance of the co‐evolutionary processes in shaping the diversity of life on Earth.

The importance of plant genotype and contemporary evolution for terrestrial ecosystem processes - Connor R. Fitzpatrick; Anurag A. Agrawal; Nathan Basiliko; Amy P. Hastings; Marney E. Isaac; Michael Preston; Marc T. J. Johnson (Ecology, 2015)
Plant genetic variation and evolutionary dynamics are predicted to impact ecosystem processes but these effects are poorly understood. Here we test the hypothesis that plant genotype and contemporary evolution influence the flux of energy and nutrients through soil, which then feedback to affect seedling performance in subsequent generations. We conducted a multiyear field evolution experiment using the native biennial plant Oenothera biennis . This experiment was coupled with experimental assays to address our hypothesis and quantify the relative importance of evolutionary and ecological factors on multiple ecosystem processes. Plant genotype, contemporary evolution, spatial variation, and herbivory affected ecosystem processes (e.g., leaf decay, soil respiration, seedling performance, N cycling), but their relative importance varied between specific ecosystem variables. Insect herbivory and evolution also contributed to a feedback that affected seedling biomass of O. biennis in the next generation. Our results show that heritable variation among plant genotypes can be an important factor affecting local ecosystem processes, and while effects of contemporary evolution were detectable and sometimes strong, they were often contingent on other ecological factors.

Experimental evidence for the effect of habitat loss on the dynamics of migratory networks - Gustavo S. Betini; Mark J. Fitzpatrick; D. Ryan Norris (Ecology Letters, 2015)
Migratory animals present a unique challenge for understanding the consequences of habitat loss on population dynamics because individuals are typically distributed over a series of interconnected breeding and non‐breeding sites (termed migratory network ). Using replicated breeding and non‐breeding populations of Drosophila melanogaster and a mathematical model, we investigated three hypotheses to explain how habitat loss influenced the dynamics of populations in networks with different degrees of connectivity between breeding and non‐breeding seasons. We found that habitat loss increased the degree of connectivity in the network and influenced population size at sites that were not directly connected to the site where habitat loss occurred. However, connected networks only buffered global population declines at high levels of habitat loss. Our results demonstrate why knowledge of the patterns of connectivity across a species range is critical for predicting the effects of environmental change and provide empirical evidence for why connected migratory networks are commonly found in nature.

Locally adapted traits maintained in the face of high gene flow - S. W. Fitzpatrick; J. C. Gerberich; J. A. Kronenberger; L. M. Angeloni; W. C. Funk (Ecology Letters, 2015)
Gene flow between phenotypically divergent populations can disrupt local adaptation or, alternatively, may stimulate adaptive evolution by increasing genetic variation. We capitalised on historical Trinidadian guppy transplant experiments to test the phenotypic effects of increased gene flow caused by replicated introductions of adaptively divergent guppies, which were translocated from high‐ to low‐predation environments. We sampled two native populations prior to the onset of gene flow, six historic introduction sites, introduction sources and multiple downstream points in each basin. Extensive gene flow from introductions occurred in all streams, yet adaptive phenotypic divergence across a gradient in predation level was maintained. Descendants of guppies from a high‐predation source site showed high phenotypic similarity with native low‐predation guppies in as few as ~12 generations after gene flow, likely through a combination of adaptive evolution and phenotypic plasticity. Our results demonstrate that locally adapted phenotypes can be maintained despite extensive gene flow from divergent populations.

Aspirated bile: a major host trigger modulating respiratory pathogen colonisation in cystic fibrosis patients - F. J. Reen; D. F. Woods; M. J. Mooij; M. N. Chróinín; D. Mullane; L. Zhou; J. Quille; D. Fitzpatrick; J. D. Glennon; G. P. McGlacken; C. Adams; F. O’Gara (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Adult vascular smooth muscle cells in culture express neural stem cell markers typical of resident multipotent vascular stem cells - Eimear Kennedy; Ciaran J. Mooney; Roya Hakimjavadi; Emma Fitzpatrick; Shaunta Guha; Laura E. Collins; Christine E. Loscher; David Morrow; Eileen M. Redmond; Paul A. Cahill (Cell and Tissue Research, 2014)

A Community-based Collaborative Approach to Improve Breast Cancer Screening in Underserved African American Women - Rachel Karcher; Dawn C. Fitzpatrick; Dawn J. Leonard; Scott Weber (Journal of Cancer Education, 2014)

Hydrology and climatology at Laguna La Gaiba, lowland Bolivia: complex responses to climatic forcings over the last 25 000 years - SARAH E. METCALFE; BRONWEN S. WHITNEY; KATHARINE A. FITZPATRICK; FRANCIS E. MAYLE; NEIL J. LOADER; F. ALAYNE STREET‐PERROTT; DAVID G. MANN (Journal of Quaternary Science, 2014)
Diatom, geochemical and isotopic data provide a record of environmental change in Laguna La Gaiba, lowland Bolivia (17°45′S, 57°35′W), over the last ca. 25 000 years. High‐resolution diatom analysis around the Last Glacial–Interglacial Transition provides new insights into this period of change. The full and late glacial lake was generally quite shallow, but with evidence of periodic flooding. At about 13 100 cal a BP, just before the start of the Younger Dryas chronozone, the diatoms indicate shallower water conditions, but there is a marked change at about 12 200 cal a BP indicating the onset of a period of high variability, with rising water levels punctuated by periodic drying. From ca. 11 800 to 10 000 cal a BP, stable, deeper water conditions persisted. There is evidence for drying in the early to middle Holocene, but not as pronounced as that reported from elsewhere in the southern hemisphere tropics of South America. This was followed by the onset of wetter conditions in the late Holocene consistent with insolation forcing. Conditions very similar to present were established about 2100 cal a BP. A complex response to both insolation forcing and millennial‐scale events originating in the North Atlantic is noted.

Alleles underlying larval foraging behaviour influence adult dispersal in nature - Allan H. Edelsparre; Anders Vesterberg; Jang H. Lim; Milad Anwari; Mark J. Fitzpatrick (Ecology Letters, 2014)
The dispersal and migration of organisms have resulted in the colonisation of nearly every possible habitat and ultimately the extraordinary diversity of life. Animal dispersal tendencies are commonly heterogeneous (e.g. long vs. short) and non‐random suggesting that phenotypic and genotypic variability between individuals can contribute to population‐level heterogeneity in dispersal. Using laboratory and field experiments, we demonstrate that natural allelic variation in a gene underlying a foraging polymorphism in larval fruit flies ( for ), also influences their dispersal tendencies as adults. Rover flies ( for R ; higher foraging activity) have consistently greater dispersal tendencies and are more likely to disperse longer distances than sitter flies ( for s ; lower foraging activity). Increasing for expression in the brain and nervous system increases dispersal in sitter flies. Our study supports the notion that variation in dispersal can be driven by intrinsic variation in food‐dependent search behaviours and confirms that single gene pleiotropic effects can contribute to population‐level heterogeneity in dispersal.

Coping with aquatic hypoxia: how the plainfin midshipman (Porichthys notatus) tolerates the intertidal zone - Paul M. Craig; John L. Fitzpatrick; Patrick J. Walsh; Chris M. Wood; Grant B. McClelland (Environmental Biology of Fishes, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Isolation and characterization of eight polymorphic microsatellite loci for Natterer’s bat, Myotis nattereri (Vespertilionidae, Chiroptera) - David D. Scott; Seán Fitzpatrick; Deborah A. Bailie; Emma S. M. Boston; Mathieu G. Lundy; Daniel J. Buckley; Emma C. Teeling; W. Ian Montgomery; Paulo A. Prodöhl (Conservation Genetics Resources, 2013)

Clinical and mutation data in 12 patients with the clinical diagnosis of Nager syndrome - J. C. Czeschik; C. Voigt; Y. Alanay; B. Albrecht; S. Avci; D. FitzPatrick; D. R. Goudie; U. Hehr; A. J. Hoogeboom; H. Kayserili; P. O. Simsek-Kiper; L. Klein-Hitpass; et al. (Human Genetics, 2013)

Doomed before they are described? The need for conservation assessments of cryptic species complexes using an amblyopsid cavefish (Amblyopsidae: Typhlichthys) as a case study - Matthew L. Niemiller; Gary O. Graening; Dante B. Fenolio; James C. Godwin; James R. Cooley; William D. Pearson; Benjamin M. Fitzpatrick; Thomas J. Near (Biodiversity and Conservation, 2013)

Low temperature constrains growth rates but not short-term ingestion rates of Antarctic ciliates - Julie M. Rose; Elizabeth Fitzpatrick; Annie Wang; Rebecca J. Gast; David A. Caron (Polar Biology, 2013)

Lethal Effects of Water Quality on Threatened California Salamanders but Not on Co‐Occurring Hybrid Salamanders - MAUREEN E. RYAN; JARRETT R. JOHNSON; BENJAMIN M. FITZPATRICK; LINDA J. LOWENSTINE; ANGELA M. PICCO; H. BRADLEY SHAFFER (Conservation Biology, 2013)
Biological invasions and habitat alteration are often detrimental to native species, but their interactions are difficult to predict. Interbreeding between native and introduced species generates novel genotypes and phenotypes, and human land use alters habitat structure and chemistry. Both invasions and habitat alteration create new biological challenges and opportunities. In the intensively farmed Salinas Valley, California (U.S.A.), threatened California tiger salamanders ( Ambystoma californiense ) have been replaced by hybrids between California tiger salamander and introduced barred tiger salamanders ( Ambystoma tigrinum mavortium ). We conducted an enclosure experiment to examine the effects habitat modification and relative frequency of hybrid and native California tiger salamanders have on recruitment of salamanders and their prey, Pacific chorus frogs ( Pseudacris regilla ). We tested whether recruitment differed among genetic classes of tiger salamanders (hybrid or native) and pond hydroperiod (seasonal or perennial). Roughly 6 weeks into the experiment, 70% (of 378 total) of salamander larvae died in 4 out of 6 ponds. Native salamanders survived ( n = 12) in these ponds only if they had metamorphosed prior to the die‐offs. During die‐offs, all larvae of native salamanders died, whereas 56% of hybrid larvae died. We necropsied native and hybrid salamanders, tested water quality, and queried the California Department of Pesticide Regulation database to investigate possible causes of the die‐offs. Salamander die‐offs, changes in the abundance of other community members (invertebrates, algae, and cyanobacteria), shifts in salamander sex ratio, and patterns of pesticide application in adjacent fields suggest that pesticide use may have contributed to die‐offs. That all survivors were hybrids suggests that environmental stress may promote rapid displacement of native genotypes . Efectos Letales de la Calidad del Agua sobre Salamandras de California Amenazadas pero no sobre Salamandras Híbridas Concurrentes

Response of diurnal and nocturnal coral reef fish to protection from fishing: an assessment using baited remote underwater video - E. S. Harvey; S. R. Dorman; C. Fitzpatrick; S. J. Newman; D. L. McLean (Coral Reefs, 2012)

Symbiodinium diversity in the soft coral Heteroxenia sp. and its nudibranch predator Phyllodesmium lizardensis - S. K. FitzPatrick; K. L. Liberatore; J. R. Garcia; I. Burghardt; D. R. Colman; S. A. Moquin; C. D. Takacs-Vesbach; U. L. Shepherd (Coral Reefs, 2012)

Hybridization between two gartersnake species (Thamnophis) of conservation concern: a threat or an important natural interaction? - John S. Placyk; Benjamin M. Fitzpatrick; Gary S. Casper; Randall L. Small; R. Graham Reynolds; Daniel W. A. Noble; Ronald J. Brooks; Gordon M. Burghardt (Conservation Genetics, 2012)

Does proximity to aquatic pollution affect reproductive traits in a wild‐caught intertidal fish? - N. M. Sopinka; J. L. Fitzpatrick; J. E. Taves; M. G. Ikonomou; S. E. Marsh‐Rollo; S. Balshine (Journal of Fish Biology, 2012)
How chronic exposure to aquatic pollution affects reproductive traits was assessed in nesting wild‐caught plainfin midshipman Porichthys notatus in areas with low and high contaminant exposure on Vancouver Island, British Columbia. Males in high‐exposure areas had a greater degree of testicular asymmetry, sperm with shorter heads and fewer live eggs in their nests. The results of this study provide important insights into the potential consequences of contaminant exposure on the reproductive physiology of wild‐caught fishes.

Assessing the potential for post‐copulatory sexual selection in elasmobranchs - J. L. Fitzpatrick; R. M. Kempster; T. S. Daly‐Engel; S. P. Collin; J. P. Evans (Journal of Fish Biology, 2012)
This review highlights the potential role that post‐copulatory sexual selection plays in elasmobranch reproductive systems and the utility of this group to further understanding of evolutionary responses to the post‐copulatory processes of sperm competition and cryptic female choice. The growing genetic evidence for female multiple mating (polyandry) in elasmobranchs is summarized. While polyandry appears to be common in this group, rates of multiple paternity are highly variable between species suggesting that there is large variance in the strength of post‐copulatory sexual selection among elasmobranchs. Possible adaptations of traits important for post‐copulatory sexual selection are then considered. Particular emphasis is devoted to explore the potential for sperm competition and cryptic female choice to influence the evolution of testes size, sperm morphology, genital morphology and sperm storage organs. Finally, it is argued that future work should take advantage of the wealth of information on these reproductive traits already available in elasmobranchs to gain a better understanding of how post‐copulatory sexual selection operates in this group.

New records for prehistoric introduction of Neotropical mammals to the West Indies: evidence from Carriacou, Lesser Antilles - Christina M. Giovas; Michelle J. LeFebvre; Scott M. Fitzpatrick (Journal of Biogeography, 2012)
Aim This paper investigates the prehistoric introduction of five mammalian taxa to Carriacou (Lesser Antilles) and refines the known anthropogenic ranges for these fauna in the pre‐Columbian West Indies. The importance of such records for understanding the region’s historical biogeography and ecology is considered. Location Carriacou Island, Grenada (12°28′ N, 61°26′ W). Methods Zooarchaeological assemblages from Carriacou’s earliest documented prehistoric sites, Grand Bay and Sabazan, were analysed, and exotic taxa were identified and quantified. The timing of introductions was established based on multiple radiocarbon assays, including three new accelerator mass spectrometry (AMS) direct dates obtained on the bone of exotic taxa. Source species and location(s) are considered and compared with known prehistoric records for the Caribbean to synthesize anthropogenic distributions for the pre‐Columbian period. The contexts of the zooarchaeological remains are evaluated to better understand the nature and purpose of introductions. Results Zooarchaeological investigation on Carriacou reveals the occurrence of multiple mammal introductions from South American between c . ad 700 and ad 1400. This paper presents the first records for guinea pig ( Cavia sp.), armadillo ( Dasypus sp.), peccary ( Tayassu/Pecari sp.), opossum ( Didelphis sp.) and agouti ( Dasyprocta sp.) from the island. Human‐mediated transport of these taxa is indicated by their absence from the record prior to human settlement of Carriacou. Several translocated species are either rare or entirely unknown for the region, and overall West Indian distributions are temporally and spatially discontinuous. Archaeological contexts indicate that mammalian introductions arose from human subsistence needs, but other social factors may have shaped the dispersal of these fauna. Main conclusions The taxonomic combination and richness of Carriacou’s introduced fauna are unusual within the region. Importantly, the new records significantly improve the known pre‐Columbian geographic range for peccary, guinea pig and armadillo. Integrated with regional records, these data augment our understanding of the Caribbean’s historical biogeography, and have the potential to improve our understanding of human mobility and anthropogenic environmental impacts in the West Indies prior to the arrival of Europeans.

Assimilation of water and dietary ions by the gastrointestinal tract during digestion in seawater-acclimated rainbow trout - Carol Bucking; John L. Fitzpatrick; Sunita R. Nadella; Iain J. McGaw; Chris M. Wood (Journal of Comparative Physiology B, 2011)

Attenuation of arthritis in rodents by a novel orally-available inhibitor of sphingosine kinase - Leo R. Fitzpatrick; Cecelia Green; Elizabeth E. Frauenhoffer; Kevin J. French; Yan Zhuang; Lynn W. Maines; John J. Upson; Emmanuel Paul; Henry Donahue; Timothy J. Mosher; Charles D. Smith (Inflammopharmacology, 2011)

A lover, not a fighter: mating causes male crickets to lose fights - Kevin A. Judge; Janice J. Ting; Jonathan Schneider; Mark J. Fitzpatrick (Behavioral Ecology and Sociobiology, 2010)

Landscape effects on extremely fragmented populations of a rare solitary bee, Colletes floralis - EMILY S. DAVIS; TOMÁS E. MURRAY; ÚNA FITZPATRICK; MARK J. F. BROWN; ROBERT J. PAXTON (Molecular Ecology, 2010)
Globally, there is concern over the decline of bees, an ecologically important group of pollinating insects. Genetic studies provide insights into population structure that are crucial for conservation management but that would be impossible to obtain by conventional ecological methods. Yet conservation genetic studies of bees have primarily focussed on social species rather than the more species‐rich solitary bees. Here, we investigate the population structure of Colletes floralis , a rare and threatened solitary mining bee, in Ireland and Scotland using nine microsatellite loci. Genetic diversity was surprisingly as high in Scottish (Hebridean island) populations at the extreme northwestern edge of the species range as in mainland Irish populations further south. Extremely high genetic differentiation among populations was detected; multilocus F ST was up to 0.53, and and D est were even higher (maximum: 0.85 and 1.00, respectively). A pattern of isolation by distance was evident for sites separated by land. Water appears to act as a substantial barrier to gene flow yet sites separated by sea did not exhibit isolation by distance. C. floralis populations are extremely isolated and probably not in regional migration‐drift equilibrium. GIS‐based landscape genetic analysis reveals urban areas as a potential and substantial barrier to gene flow. Our results highlight the need for urgent site‐specific management action to halt the decline of this and potentially other rare solitary bees.

Public health impacts of climate change in Washington State: projected mortality risks due to heat events and air pollution - J. Elizabeth Jackson; Michael G. Yost; Catherine Karr; Cole Fitzpatrick; Brian K. Lamb; Serena H. Chung; Jack Chen; Jeremy Avise; Roger A. Rosenblatt; Richard A. Fenske (Climatic Change, 2010)

Effects of Habitat Fragmentation on Effective Dispersal of Florida Scrub‐Jays - AURÉLIE COULON; JOHN W. FITZPATRICK; REED BOWMAN; IRBY J. LOVETTE (Conservation Biology, 2010)
Studies comparing dispersal in fragmented versus unfragmented landscapes show that habitat fragmentation alters the dispersal behavior of many species. We used two complementary approaches to explore Florida Scrub‐Jay (Aphelocoma cœrulescens) dispersal in relation to landscape fragmentation. First, we compared dispersal distances of color‐marked individuals in intensively monitored continuous and fragmented landscapes. Second, we estimated effective dispersal relative to the degree of fragmentation (as inferred from two landscape indexes: proportion of study site covered with Florida Scrub‐Jay habitat and mean distance to nearest habitat patch within each study site) by comparing genetic isolation‐by‐distance regressions among 13 study sites having a range of landscape structures. Among color‐banded individuals, dispersal distances were greater in fragmented versus continuous landscapes, a result consistent with other studies. Nevertheless, genetic analyses revealed that effective dispersal decreases as the proportion of habitat in the landscape decreases. These results suggest that although individual Florida Scrub‐Jays may disperse farther as fragmentation increases, those that do so are less successful as breeders than those that disperse short distances. Our study highlights the importance of combining observational data with genetic inferences when evaluating the complex biological and life‐history implications of dispersal .

Assessing reef fish assemblage structure: how do different stereo-video techniques compare? - Dianne L. Watson; Euan S. Harvey; Ben M. Fitzpatrick; Timothy J. Langlois; George Shedrawi (Marine Biology, 2010)

Geography disentangles introgression from ancestral polymorphism in Lake Malawi cichlids - MERYL C. MIMS; C. DARRIN HULSEY; BENJAMIN M. FITZPATRICK; J. TODD STREELMAN (Molecular Ecology, 2010)
Phenotypically diverse Lake Malawi cichlids exhibit similar genomes. The extensive sharing of genetic polymorphism among forms has both intrigued and frustrated biologists trying to understand the nature of diversity in this and other rapidly evolving systems. Shared polymorphism might result from hybridization and/or the retention of ancestrally polymorphic alleles. To examine these alternatives, we used new genomic tools to characterize genetic differentiation in widespread, geographically structured populations of Labeotropheus fuelleborni and Metriaclima zebra . These phenotypically distinct species share mitochondrial DNA (mtDNA) haplotypes and show greater mtDNA differentiation among localities than between species. However, Bayesian analysis of nuclear single nucleotide polymorphism (SNP) data revealed two distinct genetic clusters corresponding perfectly to morphologically diagnosed L. fuelleborni and M. zebra . This result is a function of the resolving power of the multi‐locus dataset, not a conflict between nuclear and mitochondrial partitions. Locus‐by‐locus analysis showed that mtDNA differentiation between species ( F CT ) was nearly identical to the median single‐locus SNP F CT . Finally, we asked whether there is evidence for gene flow at sites of co‐occurrence. We used simulations to generate a null distribution for the level of differentiation between co‐occurring populations of L. fuelleborni and M. zebra expected if there was no hybridization. The null hypothesis was rejected for the SNP data; populations that co‐occur at rock reef sites were slightly more similar than expected by chance, suggesting recent gene flow. The coupling of numerous independent markers with extensive geographic sampling and simulations utilized here provides a framework for assessing the prevalence of gene flow in recently diverged species.

Gene flow between an endangered endemic iguana, and its wide spread relative, on the island of Utila, Honduras: when is hybridization a threat? - Stesha A. Pasachnik; Benjamin M. Fitzpatrick; Thomas J. Near; Arthur C. Echternacht (Conservation Genetics, 2009)

Geomorphology of a dryland fluvial system: the Lower Balonne River, southern Queensland - A. L. Kernich; C. F. Pain; J. D. A. Clarke; A. D. Fitzpatrick (Australian Journal of Earth Sciences, 2009)

The effect of elbow joint centre displacement on force generation and neural excitation - Emer P. Doheny; Madeleine M. Lowery; Mark J. O’Malley; David P. FitzPatrick (Medical & Biological Engineering & Computing, 2009)

Mixed parentage in Neolamprologus pulcher groups - K. A. Stiver; J. L. Fitzpatrick; J. K. Desjardins; S. Balshine (Journal of Fish Biology, 2009)
Genetic data collected on co‐operatively breeding Neolamprologus pulcher groups from Lake Tanganyika revealed mixed parentage in 80% of the groups examined. A case (1/11) of shared maternity was detected where a subordinate female bred alongside the dominant female in a social group. Extra‐pair paternity was assigned to other dominant males who held their own social groups, but subordinate males were not found to father young in any group (0/9).

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Ejaculate expenditure and timing of gamete release in rainbow trout Oncorhynchus mykiss - J. L. Fitzpatrick; N. R. Liley (Journal of Fish Biology, 2008)
Using a novel methodology, natural ejaculate volumes of 14 male rainbow trout Oncorhynchus mykiss were compared when males were housed with one female (absence of a rival male) or with another male and one female (rival male present). Contrary to theoretical predictions, male ejaculate expenditure was not influenced by the presence of a rival male. Male gape duration was positively correlated with the volume of sperm ejaculated. Release of sperm by the male always preceded release of eggs by the female. Analysis of the timing and duration of ejaculation suggests that males may rely on the timing and proximity of gamete release to enhance fertilization success. These results are discussed in the context of sperm competition theory.

Data sets matter, but so do evolution and ecology - Matthew C. Fitzpatrick; Robert R. Dunn; Nathan J. Sanders (Global Ecology and Biogeography, 2008)

Cryptic species diversity in a widespread bumble bee complex revealed using mitochondrial DNA RFLPs - Tomás E. Murray; Úna Fitzpatrick; Mark J. F. Brown; Robert J. Paxton (Conservation Genetics, 2008)

Climate change, plant migration, and range collapse in a global biodiversity hotspot: the Banksia (Proteaceae) of Western Australia - MATTHEW C. FITZPATRICK; AARON D. GOVE; NATHAN J. SANDERS; ROBERT R. DUNN (Global Change Biology, 2008)
Climate change has already altered global patterns of biodiversity by modifying the geographic distributions of species. Forecasts based on bioclimatic envelop modeling of distributions of species suggests greater impacts can be expected in the future, but such projections are contingent on assumptions regarding future climate and migration rates of species. Here, we present a first assessment of the potential impact of climate change on a global biodiversity hotspot in southwestern Western Australia. Across three representative scenarios of future climate change, we simulated migration of 100 Banksia (Proteaceae) species at a rate of 5 km decade −1 and compared projected impacts with those under the commonly applied, but acknowledged as inadequate, assumptions of ‘full‐’ and ‘no‐migration.’ Across all climate × migration scenarios, 66% of species were projected to decline, whereas only 6% were projected to expand or remain stable. Between 5% and 25% of species were projected to suffer range losses of 100% by 2080, depending mainly on climate scenario. Species losses were driven primarily by changes in current precipitation regimes, with the greatest losses of species projected to occur in a transition zone between wet coastal areas and interior arid regions and which is projected to become more arid in the future. Because the ranges of most species tended to collapse in all climate scenarios, we found that climate change impacts to flora of southwestern Western Australia may be large, even under optimistic assumptions regarding migration abilities. Taken together, our results suggest that the future of biodiversity in southwestern Western Australia may lie largely in the degree to which this hotspot experiences increased drought and in the ability of species to tolerate such decreases in precipitation. More broadly, our study is among a growing number of theoretical studies suggesting the impacts of future climate change on global biodiversity may be considerable.

The strontium content of roe collected from spawning brown trout Salmo trutta L. reflects recent otolith microchemistry - E. M. Waite; G. P. Closs; J. Kim; B. Barry; A. Markwitz; R. Fitzpatrick (Journal of Fish Biology, 2008)
The relationship between the strontium content of the outer layers of otoliths (an indication of recent marine, estuarine or riverine habitat use) and the strontium content of roe in ripe female brown trout Salmo trutta was examined in fish collected from the Pomahaka River and the lower reaches of the Clutha River, South Island, New Zealand. A close relationship was found between the strontium content of roe and the outer layers of otoliths. This finding suggests that spawned eggs collected from redds could potentially be used to track the extent of upstream spawning migrations by anadromous brown trout.

Congruent population structure inferred from dispersal behaviour and intensive genetic surveys of the threatened Florida scrub‐jay ( Aphelocoma cœrulescens ) - A. COULON; J. W. FITZPATRICK; R. BOWMAN; B. M. STITH; C. A. MAKAREWICH; L. M. STENZLER; I. J. LOVETTE (Molecular Ecology, 2008)
The delimitation of populations, defined as groups of individuals linked by gene flow, is possible by the analysis of genetic markers and also by spatial models based on dispersal probabilities across a landscape. We combined these two complimentary methods to define the spatial pattern of genetic structure among remaining populations of the threatened Florida scrub‐jay, a species for which dispersal ability is unusually well‐characterized. The range‐wide population was intensively censused in the 1990s, and a metapopulation model defined population boundaries based on predicted dispersal‐mediated demographic connectivity. We subjected genotypes from more than 1000 individual jays screened at 20 microsatellite loci to two Bayesian clustering methods. We describe a consensus method for identifying common features across many replicated clustering runs. Ten genetically differentiated groups exist across the present‐day range of the Florida scrub‐jay. These groups are largely consistent with the dispersal‐defined metapopulations, which assume very limited dispersal ability. Some genetic groups comprise more than one metapopulation, likely because these genetically similar metapopulations were sundered only recently by habitat alteration. The combined reconstructions of population structure based on genetics and dispersal‐mediated demographic connectivity provide a robust depiction of the current genetic and demographic organization of this species, reflecting past and present levels of dispersal among occupied habitat patches. The differentiation of populations into 10 genetic groups adds urgency to management efforts aimed at preserving what remains of genetic variation in this dwindling species, by maintaining viable populations of all genetically differentiated and geographically isolated populations.

Sex and status in a cooperative breeding fish: behavior and androgens - Julie K. Desjardins; Kelly A. Stiver; John L. Fitzpatrick; Nicole Milligan; Glen J. Van Der Kraak; Sigal Balshine (Behavioral Ecology and Sociobiology, 2008)

Anthropogenic impacts to coral reefs in Palau, western Micronesia during the Late Holocene - S. M. Fitzpatrick; T. J. Donaldson (Coral Reefs, 2007)

Building on IUCN Regional Red Lists to Produce Lists of Species of Conservation Priority: a Model with Irish Bees - ÚNA FITZPATRICK; TOMÁS E. MURRAY; ROBERT J. PAXTON; MARK J. F. BROWN (Conservation Biology, 2007)
A World Conservation Union (IUCN) regional red list is an objective assessment of regional extinction risk and is not the same as a list of conservation priority species. Recent research reveals the widespread, but incorrect, assumption that IUCN Red List categories represent a hierarchical list of priorities for conservation action. We developed a simple eight‐step priority‐setting process and applied it to the conservation of bees in Ireland. Our model is based on the national red list but also considers the global significance of the national population; the conservation status at global, continental, and regional levels; key biological, economic, and societal factors; and is compatible with existing conservation agreements and legislation. Throughout Ireland, almost one‐third of the bee fauna is threatened (30 of 100 species), but our methodology resulted in a reduced list of only 17 priority species. We did not use the priority species list to broadly categorize species to the conservation action required; instead, we indicated the individual action required for all threatened, near‐threatened, and data‐deficient species on the national red list based on the IUCN's conservation‐actions template file. Priority species lists will strongly influence prioritization of conservation actions at national levels, but action should not be exclusive to listed species. In addition, all species on this list will not necessarily require immediate action. Our method is transparent, reproducible, and readily applicable to other taxa and regions.

Temperature, but not productivity or geometry, predicts elevational diversity gradients in ants across spatial grains - Nathan J. Sanders; Jean‐Philippe Lessard; Matthew C. Fitzpatrick; Robert R. Dunn (Global Ecology and Biogeography, 2007)
Aim This research aims to understand the factors that shape elevational diversity gradients and how those factors vary with spatial grain. Specifically, we test the predictions of the species–productivity hypothesis, species–temperature hypothesis, the metabolic theory of ecology and the mid‐domain effects null model. We also examine how the effects of productivity and temperature on richness depend on spatial grain. Location Deciduous forests along an elevational gradient in Great Smoky Mountains National Park, USA. Methods We sampled 22 leaf litter ant assemblages at three spatial grains, from 1‐m 2 quadrats to 50 × 50 m plots using Winkler samplers. Results Across spatial grains, warmer sites had more species than did cooler sites, and primary productivity did not predict ant species richness. We found some support for the predictions of the metabolic theory of ecology, but no support for the mid‐domain effects null model. Thus, our data are best explained by some version of a species–temperature hypothesis. Main conclusions Our results suggest that temperature indirectly affects ant species diversity across spatial grains, perhaps by limiting access to resources. Warmer sites support more species because they support more individuals, thereby reducing the probability of local extinction. Many of our results from this elevational gradient agree with studies at more global scales, suggesting that some mechanisms shaping ant diversity gradients are common across scales.

Evidence for size and sex‐specific dispersal in a cooperatively breeding cichlid fish - K. A. STIVER; J. K. DESJARDINS; J. L. FITZPATRICK; B. NEFF; J. S. QUINN; S. BALSHINE (Molecular Ecology, 2007)
African Great Lake cichlid populations are divided into thousands of genetic subpopulations. The low gene flow between these subpopulations is thought to result from high degrees of natal philopatry, heavy predation pressure, and a patchy distribution of preferred habitats. While predation pressure and habitat distribution are fairly straightforward to assess, data on dispersal distances and rates are scarce. In fishes, direct observations of dispersal events are unlikely, but dispersal can be studied using molecular markers. Using seven microsatellite loci, we examined dispersal in the cooperatively breeding cichlid fish, Neolamprologus pulcher . As this species is found in well‐defined groups clustered into subpopulations, we could assess dispersal on a narrow (within subpopulation) and broad (between subpopulation) scale. While fish were generally more related to others in their own subpopulation than they were to fish from other subpopulations, large males diverged from this pattern. Large males were more related to other large males from different subpopulations than they were to large males from their own subpopulation, suggesting more frequent dispersal by large males. Across subpopulations, relatedness between large males was higher than the relatedness among large females; this pattern was not detected in small males and small females. Within a subpopulation, individuals appeared to be preferentially moving away from relatives, and movement was unrestricted by the physical distance between groups. Our results highlight the importance of examining multiple spatial scales when studying individual dispersal biases.

The biogeography of prediction error: why does the introduced range of the fire ant over‐predict its native range? - Matthew C. Fitzpatrick; Jake F. Weltzin; Nathan J. Sanders; Robert R. Dunn (Global Ecology and Biogeography, 2007)
Aim The use of species distribution models (SDMs) to predict biological invasions is a rapidly developing area of ecology. However, most studies investigating SDMs typically ignore prediction errors and instead focus on regions where native distributions correctly predict invaded ranges. We investigated the ecological significance of prediction errors using reciprocal comparisons between the predicted invaded and native range of the red imported fire ant ( Solenopsis invicta ) (hereafter called the fire ant). We questioned whether fire ants occupy similar environments in their native and introduced range, how the environments that fire ants occupy in their introduced range changed through time relative to their native range, and where fire ant propagules are likely to have originated. Location We developed models for South America and the conterminous United States (US) of America. Methods We developed models using the Genetic Algorithm for Rule‐set Prediction (GARP) and 12 environmental layers. Occurrence data from the native range in South America were used to predict the introduced range in the US and vice versa. Further, time‐series data recording the invasion of fire ants in the US were used to predict the native range. Results Native range occurrences under‐predicted the invasive potential of fire ants, whereas occurrence data from the US over‐predicted the southern boundary of the native range. Secondly, introduced fire ants initially established in environments similar to those in their native range, but subsequently invaded harsher environments. Time‐series data suggest that fire ant propagules originated near the southern limit of their native range. Conclusions Our findings suggest that fire ants from a peripheral native population established in an environment similar to their native environment, and then ultimately expanded into environments in which they are not found in their native range. We argue that reciprocal comparisons between predicted native and invaded ranges will facilitate a better understanding of the biogeography of invasive and native species and of the role of SDMs in predicting future distributions.

Clinical and molecular genetic features of ARC syndrome - Paul Gissen; Louise Tee; Colin A. Johnson; Emmanuelle Genin; Almuth Caliebe; David Chitayat; Carol Clericuzio; Jonas Denecke; Maja Di Rocco; Björn Fischler; David FitzPatrick; Angeles García-Cazorla; et al. (Human Genetics, 2006)

The biogeography of prediction error: why does the introduced range of the fire ant over-predict its native range? - Matthew C. Fitzpatrick; Jake F. Weltzin; Nathan J. Sanders; Robert R. Dunn (Global Ecology and Biogeography, 2006)

Novel titanocene anti-cancer drugs and their effect on apoptosis and the apoptotic pathway in prostate cancer cells - K. O'Connor; C. Gill; M. Tacke; F.-J. K. Rehmann; K. Strohfeldt; N. Sweeney; J. M. Fitzpatrick; R. W. G. Watson (Apoptosis, 2006)

Seroprevalence Estimation and Risk Factors for A. marginale on Smallholder Dairy Farms in Tanzania - E. S. Swai; E. D. Karimuribo; N. H. Ogden; N. P. French; J. L. Fitzpatrick; M. J. Bryant; D. M. Kambarage (Tropical Animal Health and Production, 2005)

A Cross-sectional Study of Reproductive Performance of Smallholder Dairy Cows in Coastal Tanzania - E. S. Swai; M. J. Bryant; E. D. Karimuribo; N. P. French; N. H. Ogden; J. L. Fitzpatrick; D. M. Kambarage (Tropical Animal Health and Production, 2005)

Evidence of Positive Darwinian Selection in Putative Meningococcal Vaccine Antigens - David A. Fitzpatrick; Christopher J. Creevey; James O. McInerney (Journal of Molecular Evolution, 2005)

Chemical reduction causing land degradation. II Detailed observations at a discharge site in the Eastern Dundas Tablelands, Victoria, Australia - W. K. Gardner; J. D. Fawcett; R. W. Fitzpatrick; R. M. Norton; M. Trethowan (Plant and Soil, 2004)

Chemical reduction causing land degradation. I Overview - W. K. Gardner; J. D. Fawcett; R. W. Fitzpatrick; R. M. Norton (Plant and Soil, 2004)

Differentiation-induced HL-60 cell apoptosis: A mechanism independent of mitochondrial disruption? - B. T. Doyle; A. J. O’Neill; J. M. Fitzpatrick; R. W. G. Watson (Apoptosis, 2004)

Gonad Organochlorine Concentrations and Plasma Steroid Levels in White Sturgeon ( Acipenser transmontanus ) from the Columbia River, USA - E. P. Foster; M. S. Fitzpatrick; G. W. Feist; C. B. Schreck; J. Yates (Bulletin of Environmental Contamination and Toxicology, 2001)

Essential genes in proximal 3L heterochromatin of Drosophila melanogaster - S. Schulze; D. A. R. Sinclair; E. Silva; K. A. Fitzpatrick; M. Singh; V. K. Lloyd; K. A. Morin; J. Kim; D. G. Holm; J. A. Kennison; B. M. Honda (Molecular Genetics and Genomics, 2001)

Life and Death in the Fast Lane: Demographic Consequences of Road Mortality in the Florida Scrub‐Jay - Ronald L. Mumme; Stephan J. Schoech; Glen E. Woolfenden; John W. Fitzpatrick (Conservation Biology, 2000)
We examined the demographic consequences of road mortality in the cooperatively breeding Florida Scrub‐Jay (Aphelocoma coerulescens ), a threatened species restricted to the oak scrub of peninsular Florida. Between May 1986 and July 1995 we monitored the survival and reproductive success of a color‐banded population of jays along a two‐lane highway at Archbold Biological Station. Annual mortality of breeding adults was 0.38 on road territories, significantly higher than the rate of 0.23 for breeders on nonroad territories. High mortality on road territories appeared to be a direct result of automobile traffic per se and not a consequence of road‐induced changes in habitat characteristics. Mortality was especially high for immigrants without previous experience living along the road: in their first two years as breeders on road territories, naive immigrants experienced annual mortality of 0.50 and 0.45. From year 3 onward, however, annual mortality dropped to 0.29, not significantly different from the rate for birds on nonroad territories. This experience‐dependent decline in road mortality could be caused either by surviving jays learning to avoid automobiles or by selective mortality operating through time (demographic heterogeneity). Proximity to the road had no effect on nesting success beyond its indirect effects on breeder experience and group size. Because the mortality of 30‐ to 90‐day‐old fledglings was significantly higher on road territories than on nonroad territories, however, breeder mortality greatly exceeded production of yearlings on road territories. Roadside territories therefore are sinks that can maintain populations of Florida Scrub‐Jays only via immigration. Because Florida Scrub‐Jays do not avoid roadside habitats and may even be attracted to them, road mortality presents a difficult challenge for the management and conservation of this threatened and declining species.

In Vitro Earthworm Lumbricus terrestris Coelomocyte Assay for Use in Terrestrial Toxicity Identification Evaluation - S. W. Burch; L. C. Fitzpatrick; A. J. Goven; B. J. Venables; M. A. Giggleman (Bulletin of Environmental Contamination and Toxicology, 1999)

Wound Healing in Earthworms Lumbricus terrestris: A Cellular-Based Biomarker for Assessing Sublethal Chemical Toxicity - M. A. Cikutovic; L. C. Fitzpatrick; A. J. Goven; B. J. Venables; M. A. Giggleman; E. L. Cooper (Bulletin of Environmental Contamination and Toxicology, 1999)

Contributions of groundwater conditions to soil and water salinization - Ramsis B. Salama; Claus J. Otto; Robert W. Fitzpatrick (Hydrogeology Journal, 1999)

The imprinted domain in mouse distal Chromosome 7: reagents for mutagenesis and sequencing - Colleen D. Day; Nancy J. Smilinich; Galina V. Fitzpatrick; Pieter J. deJong; Thomas B. Shows; Michael J. Higgins (Mammalian Genome, 1999)

Equine herpesvirus genomes: Heterogeneity of naturally occurring type 4 isolates and of a type 1 isolate after heterologous cell passage - M. J. Studdert; D. R. Fitzpatrick; G. F. Browning; A. A. Cullinane; J. M. Whalley (Archives of Virology, 1986)

Modifications of the comprehensive method for total glycoalkaloid determination - T. J. Fitzpatrick; J. D. Mackenzie; P. Gregory (American Journal of Potato Research, 1978)

Potato glycoalkaloids: Increases and variations of ratios in aged slices over prolonged storage - T. J. Fitzpatrick; S. F. Herb; S. F. Osman; J. A. McDermott (American Journal of Potato Research, 1977)

A comprehensive method for the determination of total potato glycoalkaloids - T. J. Fitzpatrick; S. F. Osman (American Journal of Potato Research, 1974)

Selection potential for tuber total nitrogen and total solids content in a tetraploid breeding population - L. L. Sanford; T. J. Fitzpatrick; W. L. Porter (American Journal of Potato Research, 1971)

Chemical composition of potatoes. VIII. Effect of variety, location, and year of growth on the content of nitrogen compounds - Eugene A. Talley; Thomas J. Fitzpatrick; William L. Porter (American Journal of Potato Research, 1970)

Protein, nonprotein, and total nitrogen in seedlings of potatoes - T. J. Fitzpatrick; R. V. Akeley; J. W. White; W. L. Porter (American Journal of Potato Research, 1969)

Continued studies of the relationship of specific gravity to total solids of potatoes - T. J. Fitzpatrick; W. L. Porter; G. V. C. Houghland (American Journal of Potato Research, 1969)

Microwave finishing of potato chips: Effect on the amino acids and sugars - Thomas J. Fitzpatrick; William L. Porter (American Journal of Potato Research, 1968)

Changes in the sugars and amino acids in chips made from fresh, stored and reconditioned potatoes - Thomas J. Fitzpatrick; William L. Porter (American Journal of Potato Research, 1966)

Chemical composition of potatoes. IV. Relationship of the free amino acid concentrations to specific gravity and storage time - Eugene A. Talley; Thomas J. Fitzpatrick; William L. Porter (American Journal of Potato Research, 1964)

Studies of the relationship of specific gravity to total solids of potatoes - W. L. Porter; T. J. Fitzpatrick; E. A. Talley (American Journal of Potato Research, 1964)

Chemical composition of potatoes. III. Relationships between specific gravity and the nitrogenous constituents - Thomas J. Fitzpatrick; Eugene A. Talley; William L. Porter; Hugh J. Murphy (American Journal of Potato Research, 1964)